URGENSI PEMBENTUKAN UNDANG-UNDANG KHUSUS PERLINDUNGAN DATA PRIBADI DI INDONESIA DALAM MEWUJUDKAN HARMONISASI HUKUM PERLINDUNGAN PRIVASI DAN DATA PRIBADI DALAM ERA DIGITAL (STUDI KASUS: INDUSTRI FINANCIAL TECHNOLOGY (FINTECH) BERBASIS PEER TO PEER LENDING - Daniel E. P. Pardede; Rasji Rasji (Jurnal Hukum Adigama, 2022)
The collection and dissemination of personal data without the permission of the data owner is aviolation of a person's privacy because privacy rights include the right to determine whether or not toprovide personal data. Personal data is an asset or commodity of high economic value. Thedevelopment and growth of Financial Technology or Fintech in Indonesia then requires Indonesia tomake laws that specifically regulate and can strictly monitor and regulate the sustainability of Fintechin Indonesia. Although Fintech is very profitable for the Indonesian economy, Fintech also has the riskof violating the law because it involves many legal subjects, such as criminal, civil and administrativeviolations. Many violations are found in Fintech in Indonesia such as consumer rights violations,personal data violations, and illegal Fintech. Therefore, the urgency of the establishment of a speciallaw on the protection of personal data in Indonesia is needed, in order to realize the harmonization ofthe law on the protection of privacy and personal data in cyberspace in the digital era. Personal datain electronic systems includes protection against the collection, collection, processing, analysis,storage, display, announcement, transmission, dissemination, and destruction of personal data.